A new extracellular glutaminase and urease-free l-asparaginase from Meyerozyma guilliermondii - Ratuchne, Aline; Izidoro, Simone Cristine; Beitel, Susan Michelz; Lacerda, Lorena Tigre [UNESP]; Knob, Adriana (Springer Nature, 2023)
l-Asparaginase (l-ASNase) is a potent chemotherapeutic drug employed to treat leukemia and lymphoma. Currently, l-ASNases for therapeutic use are obtained from Escherichia coli and Dickeya chrysanthemi (Erwinia chrysanthemi). Despite their therapeutic potential, enzymes from bacteria are subject to inducing immune responses, resulting in a higher number of side effects. Eukaryote producers, such as fungi, may provide therapeutic alternatives through enzymes that induce relatively less toxicity and immune responses. Additional expected benefits from yeast-derived enzymes include higher activity and stability in physiological conditions. This work describes the new potential therapeutic candidate l-ASNase from the yeast Meyerozyma guilliermondii. A statistical approach (full factorial central composite design) was used to optimize l-ASNase production, considering l-asparagine and glucose concentration, pH of the medium, and cultivation time as independent factors. In addition, the crude enzymes were biochemically characterized, in terms of temperature and optimal pH, thermostability, pH stability, and associated glutaminase or urease activities. Our results showed that enzyme production increased after supplementing a pH 4.0 medium with 1.0% l-asparagine and 0.5% glucose during 75 h of cultivation. Under these optimized conditions, l-ASNase production reached 26.01 U mL−1, which is suitable for scale-up studies. The produced l-ASNase exhibits maximal activity at 37 °C and pH 7.0 and is highly stable under physiological conditions. In addition, M. guilliermondiil-ASNase has no associated glutaminase or urease activities, demonstrating its potential as a promising antineoplastic agent.
Keywords: Biochemical properties; Optimization; Therapeutic enzymes; Yeasts